Diversity and Inclusion in The Workplace: Beyond The Buzzwords - Abdi Fadhlan; Nur Faliza; Ervan Susilowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the relationships between organizational factors, cultural awareness, and job satisfaction within PT Kereta Api Indonesia. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis, data was collected from 67 employees to examine the direct and indirect effects of organizational culture and diversity and inclusion policies on job satisfaction, mediated by cultural awareness. The results reveal significant direct relationships between organizational culture and both cultural awareness and job satisfaction. Additionally, diversity and inclusion policies were found to directly impact job satisfaction, albeit with limited mediation through cultural awareness. These findings underscore the critical role of organizational culture in shaping employee experieoknces and perceptions, emphasizing the importance of fostering a supportive and inclusive workplace environment to enhance job satisfaction. The study provides valuable insights for organizations, including PT Kereta Api Indonesia, aiming to promote employee satisfaction and cultivate a culture of inclusivity and well-being in the workplace. Keywords : Organizational Culture, Diversity And Inclusion Policy, Job Satisfaction, Cultural Awareness